Subediting and production for journalists : print,digital, social - Holmes, Tim (Media skills, 2016)
"The new edition of Subediting and Production for Journalists is a concise, up-to-date and readable introduction to the skills of subediting for newspapers, magazines and websites. It describes how subediting had developed, from the early days of printing to the modern era of computers, the internet, and headlines by phone and explains clearly what the sub now has to do. Using practical examples from newspapers, magazines and websites Subediting for Journalists introduces the various techniques involved in subediting from cutting copy to writing captions and cover lines"--